Analisis Yuridis Perlindungan Hukum Terhadap Pekerja dengan Perjanjian Kerja Waktu Tertentu (PKWT) Menurut Undang-Undang Nomor 06 Tahun 2023 tentang Penetapan Peraturan Pengganti Undang-Undang Nomor 02 Tahun 2022 tentang Cipta Kerja Menjadi Undang-Undang. - Saleh Saepuloh; Akbar Sayudi (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Legal protection for workers with STWA contained in Law num. 06 of 2023 and its derivative regulations are essentially intended to eliminate the system of slavery, so that it will improve the welfare of workers. However, the reality shows that the positions of employers and employees are never equal. The position of the employer is stronger than the employee so that the employee is in the very weak category.This research aims to determine the STWA regulations according to Law num. 06 of 2023 and legal protection for workers with STWA. This research is a type of normative juridical research using a normative juridical approach by processing and analyzing legal materials using descriptive juridical methods.The research results show that STWA arrangements are based on the time period and completion of a particular job. STWA is based on a maximum period of 5 (five) years. STWA is based on the completion of certain work based on the agreement of the parties as stated in the work agreement. STWA based on the completion of certain work can be extended up to a certain time limit until the work is completed. Employers are obliged to provide compensation money to workers when the STWA ends. Legal protection for workers with STWA includes: protection for social security, protection for wages, and protection for industrial relations disputes. Law num. 06 of 2023 raises new problems related to STWA, namely: there is no limit to the maximum term of STWA based on the completion of certain work, there are no legal consequences if STWA is made unwritten, and there is no regulation on notification of STWA extensions.